2012
DOI: 10.1088/1674-1056/21/7/070502
|View full text |Cite
|
Sign up to set email alerts
|

Properties of train traffic flow in a moving block system

Abstract: The development direction of railways is toward the improvement of capacity and service quality, where the service quality includes safety, schedule, high speed, and comfort. In light of the existing cellular automaton models, in this paper, we develop a model to analyze the mixed running processes of trains with maximal speeds of 500 km/h and 350 km/h respectively in the moving block system. In the proposed model, we establish some sound rules to control the running processes of a train, where the rules inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Liang and Xue examined the effect of curvature, arc length, and the road surface friction coefficiency on traffic flow and reproduced the phenomenon of go-and-stop in actual traffic conditions [22]. Wang et al revealed the characteristics and laws of running speed on different types of roads and its relationship with horizontal curve radius through the analysis of different types of road running speed prediction models and pointed out horizontal curve design values for all levels of roads [23].…”
Section: Introductionmentioning
confidence: 99%
“…Liang and Xue examined the effect of curvature, arc length, and the road surface friction coefficiency on traffic flow and reproduced the phenomenon of go-and-stop in actual traffic conditions [22]. Wang et al revealed the characteristics and laws of running speed on different types of roads and its relationship with horizontal curve radius through the analysis of different types of road running speed prediction models and pointed out horizontal curve design values for all levels of roads [23].…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al proposed a cellular automaton traffic model for the four-aspect fixed autoblock systems and simulated the traffic phenomenon of train delay. They also investigated the effects of the main factors including train interval, proportion of freight train, dwell time of the train in the station, and the number of platforms [19][20][21][22][23]. Wang et al analyze the train systems under the moving block system by using the CA model.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al analyze the train systems under the moving block system by using the CA model. They proposed a new CA model to simulate the trains and achieved the needed data for the variations of section carrying capacity and the average train delay [24]. Zhou et al put forward a cellular automaton model which is used to solve the multispeed running system of the automatic blocking section and analyzed the influence of the different speed train composing rate and the overtaking distance on transporting capacity of railway section [25].…”
Section: Introductionmentioning
confidence: 99%
“…For the moving block system, more and more models for simulating the railway traffic system based on the fixed block system were proposed currently [25][26][27][28][29][30]. Zhou et al [25] simulated the traffic phenomenon of the delay propagation in a moving-like block system.…”
Section: Introductionmentioning
confidence: 99%